Ion beam studies of MBE grown GaN films on (1 1 1) silicon substrates - Alves, E.
GaN epitaxial films were grown on silicon substrates by molecular beam epitaxy under different conditions. Some of the films were doped with the rare earths (RE) Er, Eu or Tm during the growth, and were studied regarding its composition and crystalline quality. The Rutherford backscattering/channelling and heavy ion elastic recoil detection techniques were combined in order to get information on the depth distribution of all the elements present in the films. The results show that the single crystalline quality of the films improves with increasing substrate temperature and Ga flux. For these conditions the Ga concentration is the one expected for a stoichiometric film. A decrease of the Ga flux or increase in the RE cell temperature allows an increase of the concentration of the RE incorporated during the growth. The light impurity present in all the films studied, within our detection limits, was hydrogen. The angular scans along the 〈0 0 0 1〉 reveal that a fraction of the RE is incorporated into regular lattice sites of the wurtzite structure of GaN. Moreover, the optical properties of the films correlate well with the crystalline quality and the Eu doped samples show an intense red luminescence at room temperature.